The Effect of Relaxation Therapy on the Reduction of Menstrual Pain in Adolescents - Wibowo Hanafi Ari Susanto; Erna Purwanti (Professional Evidence-based Research and Advances in Wellness and Treatment, 2025)
Menstrual pain (dysmenorrhea) is one of the complaints experienced by adolescent girls and can interfere with daily activities and quality of life. Relaxation techniques are a nonpharmacological method believed to be able to reduce pain levels by reducing muscle tension and relieving stress. Purpose: This study aims to determine the effect of relaxation techniques on reducing the level of menstrual pain in adolescents. Methods: This study used a quasi-experimental design with pretest-posttest approach without a control group. Sample of 15 people who are adolescent girls experiencing dysmenorrhea and selected through purposive sampling technique. The intervention was given in the form of relaxation techniques for 5 days. The Data were analyzed using paired t-test with significance level p <0.05. Results: The mean pain level before the intervention was 6.80 ± 1.01 and decreased to 3.93 ± 1.28 after the intervention. The t-test results showed a value of t = 9.264 with p = 0.000 (p < 0.05), which means there is a significant difference between the pain levels before and after the intervention. Implications: The results of this study show that relaxation techniques are effective in reducing the level of menstrual pain in adolescents. This provides a non-pharmacological alternative used by health workers in providing care to adolescents with complaints of dysmenorrhea. Conclusion: By reducing menstrual pain through relaxation techniques, adolescents can undergo learning and social activities more optimally. This contributes to improved quality of life, self-confidence, decreased anxiety or stress that often accompanies the menstrual cycle.